If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11t+5=84-6t
We move all terms to the left:
11t+5-(84-6t)=0
We add all the numbers together, and all the variables
11t-(-6t+84)+5=0
We get rid of parentheses
11t+6t-84+5=0
We add all the numbers together, and all the variables
17t-79=0
We move all terms containing t to the left, all other terms to the right
17t=79
t=79/17
t=4+11/17
| -x/7+2=13 | | (2^x)^2-3.2^x+2=0 | | 6/1x=-3/11 | | 13=−11−(6m−11)+6m | | 100+2x=729 | | 8c+4c+c=65 | | (4x+2)+(7x-11)=90 | | 18x(3x+5=10) | | -5x+(x+6)=123,75 | | 4x2x=992 | | 21+9y=12y | | x-(2x3)=2 | | –18q+10q+16q–3=–19 | | 65=v2/5+19 | | 4/x=10-6 | | 6–p=9 | | p–6=9 | | 10^(x-3)=100000 | | 2(4.5x+4.5)=-2(2.5x-8) | | p=9–6 | | -12-6m=-(3m-3) | | 2x+20/2=18; | | 27-3a=12 | | 8.25h=429 | | 9a-3a=46 | | 12+x=-3(x-2)+3x | | 13^-x-6=6^9x | | 4x-5=14x15 | | 5/2b-2.75=7.25 | | f(1)=100 | | 7=1.5k | | y=3×-1 |